User Resistance to Digital Goods: a Case of E-books - Jongbum Kim; Jeonghun Seo (International Telecommunications Society (ITS), 2017)
Technology adoption has long been studied on the information systems field. On the contrary, why people do not adopt a new technology has not been focused. Focusing solely on the enabling factors, important additional perceptions possibly have missed. This research adopt the concept of resistance to change to explain the peoples' adoption behavior. Combined with theory of planned behavior and functional/psychological barriers that causes resistance, this study suggests a theoretical framework that can explain adoption behavior from another viewpoint. The model is validated by partial least square techniques. The barriers causes resistance to change and users with higher resistance to change have less intention to use. However, although subjective norm and self-efficacy from TPB have positive effect on intention to use, resistance to change does not mediate the relationships among them. This research expand the understanding of adoption behavior by examining inhibiting factors. The findings provide insights to the digital product providers, especially e-book publishers explaining why digital products fail in the marketplace.
Keywords: 330; Resistance to Change; E-book; Theory of Planned Behavior; Usage Barrier; Psychological Barrier